STUDY ON GREEN MARKETING WITH SPECIAL REFERENCE TO FAST MOVING CONSUMER GOODS IN KANCHIPURAM DISTRICT - DHANASEKAR R; Dr. A SANKAR (Utilitas Mathematica, 2025)
The Fast Moving Consumer Goods (FMCG) sector is an important contributor to India's GDP and it is the fourth largest sector in the Indian economy. The sector is excited about a burgeoning population whose incomes are rising which is willing to spend on goods designed to improve lifestyle. Green marketing is inevitable and it is the need of the hour. It is a creative opportunity to innovate in ways that make a difference and at the same time achieve business success by designing and modifying the products totally suitable to nature. Organisations and business however has seen change in consumer attitudes and are trying to gain an edge in the competitive market by exploiting the potential in the green market industry. However, a better understanding of consumer behaviour is necessary especially in the FMCG sector. Therefore, the study titled "Green Marketing With Special Reference To Fast Moving Consumer Goods (FMCG's)" is relevant for the companies to know the various green marketing practices followed by the FMCG companies and also the consumer's preference towards green products in the FMCG sector. This study also offers practical guidelines to marketers who are planning to target Kanchipuram district market. Even though Kanchipuram district is an agricultural based district, there is a good scope for developing thrust sector activities of green marketing equipment like pure products, edible items, fruits and vegetables on organic farming. Therefore, type of industries is going to be developed in the next five years. Qualitative approach was adopted for the study by using a questionnaire and the total sample composed of 120 respondents among the district of Kanchipuram, Furthermore, stratified random sampling was used to collect data.